IMPLEMENTASI AJARAN PANCA YAMA BRATA DALAM PEMBENTUKAN JIWA KEPEMIMPINAN PADA MAHASISWA - Wira Bawana, Dewa Gede Satria; Susilawati, Ni Putu Lidya; Sutriyanti, Ni Komang (Jurnal Penjaminan Mutu, 2025)
Panca Yama Brata is one of the ethical teachings in Hinduism that can serve as a guideline for shaping leadership qualities, especially for students. This teaching consists of five main principles: Ahimsa, Brahmacari, Satya, Asteya, and Awyawaharika, each of which holds significance in developing leadership character. Ahimsa instills the value of non-violence avoiding harm physically, emotionally, or verbally thereby fostering leaders with empathy. Brahmacari emphasizes the importance of a passion for learning and seeking knowledge as a foundation for effective leadership. Satya teaches students to uphold honesty, justice, and truth, which are essential for building trust. Asteya encourages students to refrain from stealing or taking others' rights, instead promoting integrity and respect for others. Awyawaharika stresses the importance of prioritizing truth and dharma values in every action. The implementation of Panca Yama Brata not only helps students develop exemplary leadership qualities but also creates a positive impact on their environment and society. Therefore, this teaching is highly relevant in cultivating future leaders who are characterized by integrity, fairness, and a strong sense of responsibility.